Endoscopic Feeding Access - McCormack, Michael S.; Tariq, Nabil (Digestive Disease Interventions, 2018)
The need for enteral access for nutritional support has become increasingly important. It is estimated up to a third of hospitalized patients will suffer from malnourishment. There is evidence that enteral is preferable over parenteral nutrition for improved outcomes. Various approaches for enteral access exist today including blind placement of enteral catheters, radiographically, and surgically placed catheters. However, the endoscopic approach for enteral access is a well-established, reliable, safe, and quick method of obtaining enteral access. In this review article, we will cover the various endoscopic approaches for enteral access. We believe there is no single best approach for enteral access and that it should be tailored to the individual patient. This article will cover both temporary options such as nasoenteric catheters and more permanent options such as percutaneous endoscopic stomas (gastrostomy, gastrojejunostomy, direct jejunostomy) and describe their techniques, indications, contraindications, and pitfalls. Additionally, with the rise of weight loss surgery, we will cover how to manage the patient with altered gastrointestinal anatomy. Lastly, we will also review difficult post procedure scenarios associated with all of these endoscopic methods for enteral access and how to either prevent or properly manage them.
Keywords: percutaneous endoscopic gastrostomy; percutaneous endoscopic jejunostomy; endoscopic feeding access